Congratulation letter for launching Journal of Rural Tourism - Gozali, Gozali (Journal of Rural Tourism, 2024)
I would like to express my sincere congratulations to you on the publication of the first edition of the new journal Journal of Rural Tourism. I believe that this journal represents a significant and timely contribution to the scientific literature in a field that, while growing rapidly in importance, remains underrepresented in academic discourse. Rural tourism is increasingly recognized as a vital driver of sustainable development, cultural preservation, and economic diversification in many parts of the world. In numerous countries, rural areas are no longer seen solely as agricultural zones, but as vibrant destinations that offer unique cultural experiences, natural beauty, and a slower, more mindful pace of life, qualities that are becoming ever more sought after in our fast-paced global society. A defining characteristic of rural tourism is its deep connection with local communities, traditions, and landscapes. It offers a window into ways of life that are often overlooked or undervalued, while also fostering appreciation and respect for regional identities. The challenge and opportunity lie in developing this form of tourism in ways that are both economically beneficial and culturally sensitive. Importantly, rural tourism is not just about destination marketing, it encompasses complex issues such as land use, community empowerment, heritage preservation, and environmental stewardship. These multifaceted themes deserve careful, interdisciplinary exploration, and I am confident that this journal will serve as a crucial platform for such dialogue. The Journal of Rural Tourism will undoubtedly provide valuable insights into the diverse dimensions of rural tourism and help guide both academic research and practical development strategies. It has the potential to shape a more inclusive and sustainable tourism narrative, one that centers the voices and experiences of rural communities worldwide. I wish the journal every success and look forward to its growth and continued contributions to this important field.